The history of South American land mammals: the seminal cretaceous-paleocene transition - Pascual, Rosendo (1998)
The last records of Late Cretaceous and early Paleocene (Danian-Selandian) mammals from Patagonia together with those from the early Paleocene of Bolivia, are hard evidence that the whole history of the terrestrial South american mammals followed peculiar evolutionary patterns, very different from those of other regions of the world. We recognize two large episodes, which we call the Gondwanic Stage and the South American Stage. Each results from evolutionary processes which involve genetic isolation, and appear to have been related to the two stages of geographic isolation which happened in the South American continent: as part of the Gondwana supercontinent during most of the Mesozoic, and finally as a discrete and isolated continental unit near the end of the Pliocene. The first one was characterized by communities exclusively composed of no-tribosphenic and pre-tribosphenic mammals. The second one included only tribosphenic mammals (except for one monotremata and one non-tribosphenic from the early Palaeocene, and only from Patagonia). The fisrt stage was a severe isolation from the northern continents which integrated into Lau- rasia. The second, on the other hand, was characterized by sporadic direct or indirect conexions with the Laurasian continents, or with Africa. For this reason, all mammals belonging to this second stage are regional products which, in isolation, derived from extracontinental immigrants. The drastic compositional changes between these stages should have happened between the Campanian and Danian, but we lack records which would allow the recognition of their modus operandi.